The impact of COVID‐19 pandemic on people with mild cognitive impairment/dementia and on their caregivers. (13th November 2020) - Tsapanou, Angeliki; Papatriantafyllou, John D.; Yiannopoulou, Konstantina; Sali, Dimitra; Kalligerou, Fedra; Ntanasi, Eva; Zoi, Panagiota; Margioti, Eleni; Kamtsadeli, Vasiliki; Hatzopoulou, Maria; Koustimpi, Maria; Zagka, Athina; et al.
Abstract: Background: The novel coronavirus disease (COVID‐19) was first detected in Mainland China in December 2019, and soon it spread throughout the world, with multiple physical and psychological consequences across the affected populations. Aims: The aim of the current study was to analyze the impact of COVID‐19 pandemic on older adults with mild cognitive impairment (MCI)/dementia and their caregivers as well. Materials and Methods: Two hundred and four caregivers took part in the study, completing a self‐reported questionnaire about the person with MCI/dementia and their own, since the lockdown period which started in February and ended in May of 2020 in Greece. Results: Results indicated a significant overall decline of the people with MCI/dementia. Further, the domains in which people with MCI/dementia were mostly affected were: communication, mood, movement and compliance with the new measures. Caregivers also reported a great increase in their psychological and physical burden during this period, where the available support sources were limited. Discussion: The pandemic threatens to disrupt the basic routines that promote mental and physical health of both people with MCI/dementia and t heir caregivers. Conclusion: Further measures to protect and provide support to people who suffer and their families are needed.